2015
DOI: 10.1124/mol.114.097394
|View full text |Cite
|
Sign up to set email alerts
|

Cytochromeb5Is a Major Determinant of Human Cytochrome P450 CYP2D6 and CYP3A4 Activity In Vivo

Abstract: The cytochrome P450-dependent mono-oxygenase system is responsible for the metabolism and disposition of chemopreventive agents, chemical toxins and carcinogens, and .80% of therapeutic drugs. Cytochrome P450 (P450) activity is regulated transcriptionally and by the rate of electron transfer from P450 reductase. In vitro studies have demonstrated that cytochrome b 5 (Cyb5) also modulates P450 function. We recently showed that hepatic deletion of Cyb5 in the mouse (HBN) markedly alters in vivo drug pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…5) pharmacokinetics were determined in vivo in CYP3A4-HBN and CYP2D6-HBN mice, respectively, metabolism was again shown to be profoundly reduced in mice lacking hepatic b 5 , with significant increases in C max and AUC and decreased clearance relative to control animals. The minor perturbations in hepatic lipids reported in the CYP3A4-HBN and CYP2D6-HBN mice (Henderson et al, 2015) strongly support the view that the effects observed on drug disposition in vivo are not a result of changes to the lipid composition of the ER but rather reflect the consequences of a lack of b 5 . It is thus possible that the expression of b 5 , and its functionality, may make a significant contribution to the observed heterogeneity in plasma levels of many commonly prescribed drugs.…”
Section: Role Of Nadph-supporting
confidence: 61%
See 2 more Smart Citations
“…5) pharmacokinetics were determined in vivo in CYP3A4-HBN and CYP2D6-HBN mice, respectively, metabolism was again shown to be profoundly reduced in mice lacking hepatic b 5 , with significant increases in C max and AUC and decreased clearance relative to control animals. The minor perturbations in hepatic lipids reported in the CYP3A4-HBN and CYP2D6-HBN mice (Henderson et al, 2015) strongly support the view that the effects observed on drug disposition in vivo are not a result of changes to the lipid composition of the ER but rather reflect the consequences of a lack of b 5 . It is thus possible that the expression of b 5 , and its functionality, may make a significant contribution to the observed heterogeneity in plasma levels of many commonly prescribed drugs.…”
Section: Role Of Nadph-supporting
confidence: 61%
“…Using substrates for human CYP3A4 (triazolam) and CYP2D6 (debrisoquine), it was shown in vitro in hepatic microsomes that the metabolism of these drugs was significantly reduced in the absence of b 5 . Moreover, in both cases, addition of exogenous b 5 to reaction mixtures restored activity in a dose-dependent manner (Henderson et al, 2015). When triazolam (Fig.…”
Section: Role Of Nadph-mentioning
confidence: 99%
See 1 more Smart Citation
“…Since POR is present in the endoplasmic reticulum (ER) at sub-stoichiometric amounts compared to CYP, it has been proposed that their interactions involve transient oligomeric complexes (Backes and Kelley, 2003). In contrast to POR, the small hemoprotein cytochrome b5 (CYB5), which is located together with CYB5-reductase and the other components on the cytoplasmic side of the ER, is not an obligatory electron donor for CYPs but acts as modulator of enzyme activity in CYP- and sometimes substrate-dependent way (Henderson et al, 2015). For a long time, POR and CYB5 were the only proteins known to functionally interact with CYPs during the microsomal monooxygenase reaction.…”
Section: Introductionmentioning
confidence: 99%
“…4B) but exhibited large variability. Considering that CYP2D6 activity can be regulated by the rate of electron transfer from CPR and Cyb5 (Henderson et al, 2015), we measured the activity of CPR and the content of Cyb5 in S9 fractions. Neither CPR activity nor Cyb5 content in hepatic S9 fractions differed between the control and CA-fed groups (Fig.…”
Section: Cyp2d6 Induction By Cholic Acid Feedingmentioning
confidence: 99%